Everyday Life Attention Scale (ELAS): Normative data of n = 1, 874 Dutch participants. Issue 2 (4th March 2021) - Fuermaier, Anselm B. M.; Groen, Yvonne; Tucha, Lara; Weisbrod, Matthias; Aschenbrenner, Steffen; Tucha, Oliver
Abstract: The Everyday Life Attention Scale (ELAS) is a sensitive and reliable self-report questionnaire assessing attentional capacities of respondents in nine different situations of daily life. The ELAS has the potential to add relevant information to the clinical evaluation of attention deficits, to guide treatment planning, as well as to evaluate treatment outcome. The present study provides normative data of 1, 874 Dutch speaking participants, ranging from 18 to 76 years of age, with mixed levels of education and a roughly equal distribution in gender. Normative data are calculated based on multiple linear regression models for each of the nine ELAS situations. In this article, the ELAS questionnaire as well as norm data are offered free of use. Use of normative ELAS data as presented in this study enables its use in clinical practice and research. Potential applications of the ELAS and future directions are discussed.